KECERDASAN MAJEMUK: STUDI KASUS MELALUI IMPLEMENTASI MODEL PEMBELAJARAN PJBL MATERI IPAS SISWA KELAS IV SD NEGERI 014 LONG KALI - Nurhasdira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Implementation of Project-Based Learning (PjBL) in Grade IV at SD Negeri 014 Long Kali Still Faces Challenges.Therefore, the purpose of this study is to explore the implementation of the Project-Based Learning (PjBL) model used by teachers in relation to enhancing students' multiple intelligences in Grade IV at SD Negeri 014 Long Kali. The research method employed is qualitative research, with respondents consisting of teachers, students, and the principal. The respondents were selected through purposive sampling based on the research objectives. Snowball sampling occurred through the involvement of additional participants identified via the main respondents. The research procedure began with the researcher preparing instruments and learning tools based on the Project-Based Learning (PjBL) model. The research was conducted using interview and observation techniques. Data were analyzed through preliminary and final conclusions formulated during the interview process. The results of the study showed that the teacher respondent had prepared, implemented, and evaluated the results of the PjBL implementation in Grade IV at SD Negeri 014 Long Kali. The student respondents had prepared for, participated in, and achieved learning outcomes in the form of enhanced multiple intelligences. The principal respondent had facilitated the planning, implementation, and evaluation of the Project-Based Learning (PjBL), which contributed to the improvement of students' multiple intelligences.